2014
DOI: 10.1121/1.4836115
|View full text |Cite
|
Sign up to set email alerts
|

Exposure-response relationships for annoyance due to freight and passenger railway vibration exposure in residential environments

Abstract: In this work, exposure-response relationships for annoyance due to freight and passenger railway vibration exposure in residential environments are developed, so as to better understand the differences in human response to these two sources of environmental vibration. Data for this research come from a field study comprising interviews with respondents and measurements of their vibration exposure (N ¼ 752). A logistic regression model is able to accurately classify 96% of these measured railway vibration signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Even within the railway, differences in response to vibration exposure from passenger and freight traffic have been demonstrated by Sharp et al (2014) based on the data analyzed in this paper. Although it may be the case that separate relationships are needed for the two sources, there are a number of factors which may explain the observed differences in the response to the two sources.…”
Section: Applicability To Other Sources Of Vibration and Adverse Ementioning
confidence: 90%
“…Even within the railway, differences in response to vibration exposure from passenger and freight traffic have been demonstrated by Sharp et al (2014) based on the data analyzed in this paper. Although it may be the case that separate relationships are needed for the two sources, there are a number of factors which may explain the observed differences in the response to the two sources.…”
Section: Applicability To Other Sources Of Vibration and Adverse Ementioning
confidence: 90%
“…It has previously been reported that increases in noise and vibration exposure lead to increased levels of annoyance in residential environments [1,2,3,4,5]. The relationship between exposure and annoyance is, however, weak, suggesting that other factors need to be taken into account [6].…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have been carried out regarding the annoyance of vibration from transport in residential areas (Klaeboe et al, 2003;Waddington et al, 2014). Objective parameters of exposure do not fully account for the annoyance reported from vibration (Peris et al, 2014;Sharp et al, 2014;Janssen et al, 2015;Woodcock et al, 2015 under review), a finding that applies to annoyance from noise too (Guski et al, 1999).…”
Section: Introductionmentioning
confidence: 99%